Proposta de sequência didática, em consonância com a BNCC/DRC-MT, para o ensino de termodinâmica via estação meteorológica - Nascimento, Maria Aparecida Ribeiro Matos do (2022)
The present research paper sought to discuss and present evidences about the possibilities of using technological tools, in a significant way, in Physics teaching, particularilly in Thermodynamics in the theme: Matter and Energy, whose problem lies in understanding and interpreting, in relevant mode, the thermodynamic variables while phenomenological processes in macroscopic systems. In this sense, this work had as objective to make use of free access and low cost technological tools, in the construction of two weather station prototypes for monitoring thermodynamic variables in a meaningful way, considering the local environment, with and without vegetation cover. To carry out this work, methodologically, it was necessary to develop a Teaching Sequence (DS), in consonance with the BNCC/DRC-MT, containing twelve lessons, in a second year class of regular High School in the evening period. By means of the application of this proposal, although the many obstacles, it was evident the enthusiasm of students to manipulate, analyze and interpret, the thermodynamic variables involved in the data obtained through the prototypes weather station.